A Review on Medicinal Herbal Plant: Nyctanthes Arbortristis LINN. - Mobiya, Ashok Kumar; Kewatkar, Shailesh M; Jain, Vidhi; Saluja, Manmeet Singh (Journal of Biomedical and Pharmaceutical Research, 2023)
Night jasmine, often called Parijat, is the common name for Nyctanthes arbortristis Linn. The plant belongs to the Oleaceae family. The shrub is native to the tropics and subtropics of the globe. It may seem like a pretty shrub, but it really has a lot of useful medicinal and pharmacological characteristics. The plant's distribution, phytochemical make-up, and pharmacological actions are all covered in this review article.